2022
DOI: 10.3389/fpubh.2022.699321
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Proportion of Gastrointestinal Emergency Endoscopy and Peptic Ulcer Disease During the COVID-19 Pandemic: A Local Retrospective Observational Study From Vietnam

Abstract: ObjectivesThe coronavirus disease 2019 (COVID-19) pandemic has disrupted the practice of gastrointestinal (GI) endoscopy units and may increase the risk of digestive disorders. We described the situational changes in GI endoscopy and peptic ulcer disease (PUD) proportion during COVID-19 in Vietnam and examined the associated factors.MethodsA retrospective ecological study was conducted on data of Hanoi Medical University Hospital, Vietnam. The number of upper GI endoscopy and the proportion of GI emergency end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…The positive correlation between COVID-19 and the incidence of peptic ulcers was suggested by the study of Dao et al, which showed that the incidence of peptic ulcers was significantly higher during the COVID-19 pandemic in 2020 compared to 2019 in the same health facility in Vietnam [ 4 ], and by the study of Jian et al, which confirmed the same findings in two hospitals in Wuhan, China, during the pandemic [ 5 ].…”
Section: Discussionmentioning
confidence: 74%
“…The positive correlation between COVID-19 and the incidence of peptic ulcers was suggested by the study of Dao et al, which showed that the incidence of peptic ulcers was significantly higher during the COVID-19 pandemic in 2020 compared to 2019 in the same health facility in Vietnam [ 4 ], and by the study of Jian et al, which confirmed the same findings in two hospitals in Wuhan, China, during the pandemic [ 5 ].…”
Section: Discussionmentioning
confidence: 74%
“…In addition, some other studies investigated the impact of the COVID-19 pandemic on the incidence of peptic ulcer disease. For example, research by Dao et al observed that the proportion of peptic ulcer disease was significantly higher during the time of the state of emergency due to the ongoing COVID-19 pandemic in 2020 when compared to 2019 at the same health facility in Vietnam [ 75 ]. In line with Dao et al’s study, Jian et al observed that the rate of peptic ulcer disease increased dramatically in two hospitals in Wuhan, China, in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…En uso de anticoagulantes y esteroides en los pacientes de UCI en área COVID pudiesen aumentar el riesgo de desarrollo de ulceras gástricas y duodenales, sin embargo, no hubo diferencia estadísticamente significativa, al igual que lo reportado por Dao H. et al 18 y Trinidade et al 19 , por lo que fuesen necesarios estudios estadísticamente más robustos, lo que fue limitado por un contexto de emergencia sanitaria mundial.…”
Section: Pág 7721unclassified